2017
DOI: 10.3390/ijms18112247
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Neuroprotective Strategies during Hypovolemia and Hemorrhagic Shock

Abstract: Severe trauma constitutes a major cause of death and disability, especially in younger patients. The cerebral autoregulatory capacity only protects the brain to a certain extent in states of hypovolemia; thereafter, neurological deficits and apoptosis occurs. We therefore set out to investigate neuroprotective strategies during haemorrhagic shock. This review was performed in accordance to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. Before the start of the search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 68 publications
(170 reference statements)
0
3
0
Order By: Relevance
“…While the hypothesis that serelaxin might be beneficial in acute heart failure was proved wrong [12,13], serelaxin exhibits no negative impact on hemodynamic effects under normal conditions or during hypoxia or hypovolemia [14][15][16]. Currently, there is a lack of specific neuroprotective strategies for hypovolemia [17].…”
Section: Introductionmentioning
confidence: 99%
“…While the hypothesis that serelaxin might be beneficial in acute heart failure was proved wrong [12,13], serelaxin exhibits no negative impact on hemodynamic effects under normal conditions or during hypoxia or hypovolemia [14][15][16]. Currently, there is a lack of specific neuroprotective strategies for hypovolemia [17].…”
Section: Introductionmentioning
confidence: 99%
“…Neurological deficits and impairments are in many cases accompanied by a significant decrease in the patients' quality of life and capability to uphold their former lifestyle, both in regard to private and work-related matters. Since the brain is especially vulnerable to ischemia [ 1 ], a variety of medical emergencies can lead to global ischemia and result in neurological damages, for example trauma [ 2 4 ], cardiac arrest [ 1 ], cerebral stroke [ 5 ] and (albeit rarer) traumatic asphyxia [ 6 , 7 ]. Secondary damage of the brain cells can furthermore occur due to reperfusion injury [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…SYRCLE’s RoB tool was used to assess the risk of bias of included studies on animal experiments, the following results were obtained [ 34 ]: 100% of the included studies reported baseline characteristics, none of the studies provided details about sequence generation or allocation concealment, 100% reported information about random housing, 100% showed a low risk of bias in performance blinding, 10.0% of the included studies showed an unclear risk of bias in random outcome assessment, 70.0% showed a low risk of bias in detection blinding, 80.0% of studies showed a low risk of bias in incomplete outcome data, 100% showed a low risk of bias in selective outcome reporting, and none of the included studies reported other sources of bias.…”
Section: Resultsmentioning
confidence: 99%